2016
DOI: 10.1093/mutage/gew064
|View full text |Cite
|
Sign up to set email alerts
|

Weak silica nanomaterial-induced genotoxicity can be explained by indirect DNA damage as shown by the OGG1-modified comet assay and genomic analysis

Abstract: In a previous study, 15-nm silica nanoparticles (NPs) caused small increases in DNA damage in liver as measured in the in vivo comet and micronucleus assays after intravenous administration to rats at their maximum tolerated dose, a worst-case exposure scenario. Histopathological examination supported a particle-induced, tissue damage-mediated inflammatory response. This study used a targeted approach to provide insight into the mode of action (MoA) by examining transcriptional regulation of genes in liver in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In the study by Downs et al (2012), SAS (15 nm and 55 nm; SSA: 200 m 2 /g and 50 m 2 /g) caused a small, but significant increase in DNA damage in liver (15 nm SAS) and circulating micronucleated reticulocytes (both 15 and 55 nm SAS) when intravenously tested at the maximum tolerated dose (3 consecutive daily administrations at 50 mg/kg b.w., with evaluation 3 hours after the last administration). The same 15 nm SAS induced no significant effects in the standard Comet assay in liver, but induced a statistically significant increase in liver DNA damage evaluated by the hOGG1 Comet assay, which involves an oxidative damage probably induced as a consequence of the inflammatory response (Pfuhler et al 2017). In contrast, Guichard et al (2015) reported no genotoxicity (Comet and micronucleus assays) in rats administered three consecutive daily intravenous doses of 24.7 nm SAS (SSA: 204 m 2 /g) up to 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 86%
“…In the study by Downs et al (2012), SAS (15 nm and 55 nm; SSA: 200 m 2 /g and 50 m 2 /g) caused a small, but significant increase in DNA damage in liver (15 nm SAS) and circulating micronucleated reticulocytes (both 15 and 55 nm SAS) when intravenously tested at the maximum tolerated dose (3 consecutive daily administrations at 50 mg/kg b.w., with evaluation 3 hours after the last administration). The same 15 nm SAS induced no significant effects in the standard Comet assay in liver, but induced a statistically significant increase in liver DNA damage evaluated by the hOGG1 Comet assay, which involves an oxidative damage probably induced as a consequence of the inflammatory response (Pfuhler et al 2017). In contrast, Guichard et al (2015) reported no genotoxicity (Comet and micronucleus assays) in rats administered three consecutive daily intravenous doses of 24.7 nm SAS (SSA: 204 m 2 /g) up to 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, chronic exposure to silica has directly been attributed to irreversible pulmonary inflammatory disease resulting in lung tumour growth in mice [39]. A recent study aiming to provide insight into the mode of action of DNA damage caused by 15 nm silica particles in rat livers highlighted that observed DNA damage was a direct consequence of oxidative damage caused by the initiation of an immune response in the tissue [34]. These in vivo studies are supportive of the principle demonstrated in this investigation; that secondary genotoxicity promoted by NM-immune cell interaction should be an important consideration when assessing the DNA damage potential of NMs.…”
Section: Resultsmentioning
confidence: 99%
“…The genotoxicity of NMs and mechanisms leading to transient or permanent genetic changes have been intensively investigated [ 8 , 9 , 10 , 11 , 12 , 13 ]. Recent studies show that NM genotoxicity can result from two main mechanisms; primary (direct or indirect) or secondary genotoxicity.…”
Section: General Mechanisms Of Genotoxicitymentioning
confidence: 99%
“…Standard in vitro genotoxicity tests are typically based on a single cell type. However, a key observation in in vivo genotoxicity studies conducted with NMs is that the permanent changes induced in DNA are often the result of secondary genotoxicity associated with inflammation [ 8 , 9 , 10 , 11 ]. Thus, there has been a strong effort in recent years to develop more complex, in vivo-like in vitro models based on 3D structures either of a single cell type or as co-cultures of two or more cell types.…”
Section: Introductionmentioning
confidence: 99%